Post-liberalisation India: How free is the media? - Smita Gupta (South Asia: Journal of South Asian Studies, n.s., Vol.XXVIII, no.2, August 2005, 2005)
The future of censorship is very bright in India-in media, culture and intellectual life. Do not be taken in by political postures and academic correctness-politicians, the bureaucracy, the literati and the middle class love censorship. They all want freedom for their own ideas, lifestyles and moral codes; censorship for that of others